Problematika Peserta Didik dalam Menghafal Al-Quran di MAN 3 Agam Kubang Putih - Putra, Bobi; Hayati, Hayati (ANWARUL, 2023)
The main problem of the research here is the lack of motivation in students to memorize the Al-Quran. Then there are still many students' mistakes in reading the Koran, both in terms of its makhraj, short length and the rules for reading the Koran from students so that it makes it difficult for students to memorize the Koran. The research method used by researchers is descriptive qualitative research, namely data collected in the form of words, pictures, not numbers. The key informants are students, while the supporting informants are PAI teachers and other teachers. The techniques used to collect data are observation, interviews and documentation. To analyze the data, researchers used Miles and Huberman's analysis techniques, namely Data Reduction, Data Display (data display), and Conclusion Drawing or verification. In order for the data collected to be valid, the researcher uses the validity technique by means of triangulation. Based on the results of research found in the field, in terms of implementation, the process or stages that students go through are going quite well. However, there are various problems faced by students in memorizing the Qur'an both internally and externally. From an internal perspective, it can be seen from a feeling of laziness or lack of motivation within oneself, not focusing when memorizing the Al-Quran, not repeating memorization (Murajaah) at home and so on. Meanwhile, from an external perspective, it is because of friends' distractions, more focus on playing with cellphones, lots of school assignments, and not being able to divide time properly and effectively. Therefore, to overcome these problems, students need to instill sincere intentions in their hearts and earnestly memorize the Al-Quran. Besides that, it is also expected that parents and teachers can work together in increasing the potential for memorizing the Al-Quran of students. so that students in the future are even more proficient in reading and memorizing the Al-Quran.